The FIFA 11+ does not alter physical performance of amateur futsal players - Lopes, M.; Simões, D.; Rodrigues, J. M.; Costa, R.; Oliveira, J.; Ribeiro, F. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The ability of the FIFA 11+ to enhance performance has demonstrated controversial results. Hence, we examined the short and long-term effects of the FIFA 11+ on performance in male amateur futsal players. METHODS: Seventy-one male futsal players from six amateur clubs were recruited and randomized to an intervention (N.=37, age: 27.0±5.1 years) or a control group (N.=34, age: 26.0±5.1 years). The intervention group was submitted to 10 weeks of FIFA 11+ injury prevention program, 2 sessions/week, followed by a 10-week follow-up period, while the control group performed regular futsal warm-ups during the training sessions. During the follow-up period both groups performed only regular warm-ups during their training sessions. Physical performance was assessed by measuring agility (T-test), sprint (30 m sprint), flexibility (sit-and-reach test) and vertical jump performance (squat jump). RESULTS: Differences between groups were found at baseline for training exposure, body mass index, body weight, flexibility, and sprint. The results of the effect of the FIFA 11+ on the sit-and-reach test, speed and agility did not show differences pre-post intervention, as well as for the 10-week follow-up. Jump performance, showed a significant difference in favor of the control group for the intervention period and the follow-up (crude ß: -0.04 [95% CI: -0.06; -0.01]; -0.03 [95% CI: -0.06; -0.00], respectively), however after adjustment for the baseline differences the confidence interval fell out of the range of significance for the intervention and follow-up period (adjusted ß, -0.05 [95% CI: -0.10; 0.00]; -0.05 [95% CI: -0.10; 0.04]). CONCLUSIONS: The present study has shown no short and long-term performance enhancement in sprint, flexibility, agility and jump performance after the FIFA 11+ in male amateur futsal players.